Gamified Spaced Repetition for Technical Vocabulary Learning in Vocational Engineering Education: A Quasi-Experimental Study - Alviani Alviani; Andi Wafda (Faculty of Education and Teacher Training of UIN Palopo, 2025)
The abstract This research aims to analyze the effectiveness of gamification-based spaced repetition in improving the mastery and retention of civil engineering vocabulary among students of Politeknik Dewantara Palopo. The research method employed is a quasi-experimental design with experimental and control groups. The instruments used include a civil engineering vocabulary test and a motivation questionnaire. The results show a significant improvement in vocabulary mastery in the experimental group using gamified spaced repetition media. This research contributes to the application of technology-based learning methods to enhance the quality of vocational education. Furthermore, it suggests that the integration of gamification with spaced repetition provides a more engaging and effective learning environment, promoting better retention and long-term recall of technical vocabulary. The study also highlights the importance of incorporating modern educational technologies in vocational education to address the challenges of traditional learning methods. This study provides empirical evidence of the potential benefits of using gamification-based spaced repetition techniques in improving vocabulary acquisition in technical fields such as civil engineering, contributing to the advancement of educational practices in vocational training settings. As such, it has significant implications for curriculum development and the enhancement of teaching methodologies in technical education.